MTPA- and MSM-based vibration transfer of 6-DOF manipulator for anchor drilling - Liu, Youyu (Strojniški vestnik, 2022)
An anchor drilling for a coal mine support system can liberate an operator from heavy work, but will cause serious vibration, which willbe transmitted to the pedestal from the roof bolter along a manipulator. Based on the multi-level transfer path analysis (MTPA) and modal superposition method (MSM), a vibration transfer model for the subsystem composed of the joints of a manipulator with six degrees of freedom (DOF) was established. Moreover, its frequency response function matrix was also built. The 6-DOF excitation of the roof bolter was deduced. The exciting force on the roof bolter transmitted to the pedestal along the 6-DOF manipulator was analysed with a force Jacobian matrix, to identify the external loading on the pedestal. A case in engineering practice shows that the amplitude of each DOF of the pedestal from large to small is as follows: bending vibration (component 1), longitudinal vibration, torsional vibration, bending vibration (component 2), rotational vibration around z-axis, rotational vibration around y-axis. The pedestal is mainly in the form of bending vibration. The theory of vibration transfer along the 6-DOF manipulator for anchor drilling proposed in this article can provide a theoretical foundation for the development of vibration-damping techniques and the design of absorbers.
Keywords: force jacobian matrix; Jacobijeva matrika sil; manipulatorji; manipulators; metoda modalne superpozicije; modal superposition method; multi-level transfer path analysis; prenos vibracij; stroji za sidranje; večstopenjska analiza prenosne poti; vibration transfer